STUDI KESESUAIAN LAHAN TANAMAN CABAI MERAH DI KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK - kurnia, teguh dwi; Hermon, Dedi (JURNAL BUANA, 2024)
The objective of this research is to determine: 1) To identify the characteristics of land suitability for red chili farming in Lembah Gumanti District, 2) To assess the potential land suitability for red chili farming in Lembah Gumanti District. This research falls under the quantitative category. The data used in this study consists of secondary data, which includes primary data such as soil texture, drainage, pH, slope, soil depth, and temperature, along with field observations. The analysis techniques employed include the Overlay Method and the matching method using scoring. The results of this study indicate that land suitability for chili cultivation in Lembah Gumanti District falls within the category of very suitable (S1), covering an area of 11,150 ha, as well as moderately suitable (S2), covering an area of 13,875 ha. This area is highly suitable for chili cultivation, as the land suitability map indicates two main classes, namely S1 (very suitable) and S2 (moderately suitable) for chili cultivation. Lembah Gumanti District has great potential for red chili cultivation. The district is comprised of 13 land units with varying criteria, indicating that the land in Lembah Gumanti District is highly suitable for red chili farming.